2018
DOI: 10.1016/j.cbpa.2018.03.017
|View full text |Cite
|
Sign up to set email alerts
|

Molecular imaging agents for ultrasound

Abstract: Ultrasound (US) imaging is a safe, sensitive and affordable imaging modality with a wide usage in the clinic. US signal can be further enhanced by using echogenic contrast agents (UCAs) which amplify the US signal. Developments in UCAs which are targeted to sites of disease allow the use of US imaging to provide molecular information. Unfortunately, traditional UCAs are too large to leave the vascular space limiting the application of molecular US to intravascular markers. In this mini review, we highlight the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
50
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(51 citation statements)
references
References 51 publications
0
50
0
Order By: Relevance
“…The objective of this review is to provide an overview of the use of CEUS for quantification of tissue perfusion in general, as well as organ‐specific applications, advantages, and limitations. Aside from perfusion imaging, CEUS has been applied in clinical practice for visualizing specific anatomical structures, for molecular imaging and used as therapeutic agent to allow site‐specific drug delivery . However, these applications of CEUS have been extensively reviewed elsewhere and are beyond the scope of this review.…”
Section: Introductionmentioning
confidence: 99%
“…The objective of this review is to provide an overview of the use of CEUS for quantification of tissue perfusion in general, as well as organ‐specific applications, advantages, and limitations. Aside from perfusion imaging, CEUS has been applied in clinical practice for visualizing specific anatomical structures, for molecular imaging and used as therapeutic agent to allow site‐specific drug delivery . However, these applications of CEUS have been extensively reviewed elsewhere and are beyond the scope of this review.…”
Section: Introductionmentioning
confidence: 99%
“…However, its resolution is poor, at least if one wants to visualize microscopic structures (Ng and Swanevelder 2011). The main problem is a low signal-to-noise ratio due to scattering, which is currently sought out to be improved by employing so-called echogenic contrast agents that may serve as signal amplifiers (Zlitni and Gambhir 2018). Other methods with similar strengths and weaknesses are magnetic resonance imaging (MRI) and magnetic particle imaging (MPI) (Weizenecker et al 2009).…”
Section: R92mentioning
confidence: 99%
“…The application of ultrasound contrast agents (UCAs) enhances the ultrasound signal and further improves the accuracy of diagnosis. The UCAs used in clinics are typically gasfilled micron-sized bubbles (MBs) with a diameter of 1-8 μm and a limited in vivo circulation time, so these MBs cannot extravasate beyond the vasculature [2]. It has been reported that nano-scaled particles can extravasate beyond the vasculature and passively accumulate in the tumor microenvironment via enhanced permeation and retention (EPR).…”
Section: Introductionmentioning
confidence: 99%
“…The advancements in nanomedicine resulted in a rapid development of echogenic and biocompatible nano UCAS (nUCAs) (50-600 nm) with promising physical properties. These particles are composed of a phospholipid-based shell and/or polymer-based shell and a solid, liquid, or gas core [2]. Among various nUCAs, nanodroplets (NDs) have attracted a lot of attention due to their unique phase transition properties.…”
Section: Introductionmentioning
confidence: 99%